PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN KJKS BMT TAMZIS BANDUNG - Adinata, Ujang Wawan Sam (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The research objective is to be achieved (1) To know how transformational leadership, motivation and organizational culture, and (2) To in identifying the effect of transformational leadership, motivation and organizational culture on performance. The study populations were employees of BMT TAMZIS KJKS BANDUNG. Analysis of data using Path Analysis. Based on the research results it can be concluded that the transformational leadership, motivation, organizational culture significantly influence performance KJKS Employees BMT TAMZIS Bandung. The most dominant influence is the influence of organizational culture, while the lowest was transformational leadership. All the variables simultaneously affect the performance of the Employee KJKS BMT TAMZIS Bandung where the influence simultaneously by 78% while the rest influenced by other factors not included in this study. Thus the company in this case KJKS BMT TAMZIS Bandung need to increase the role of a strong organizational culture so as to improve the performance of employees. Keywords: transformational leadership, motivation, organizational culture, performance.